2008
DOI: 10.1353/pla.2008.0008
|View full text |Cite
|
Sign up to set email alerts
|

Academic/Research Librarians with Subject Doctorates: Data and Trends 1965–2006

Abstract: The topic of academic/research librarians with subject doctorates is largely unexplored in the literature, despite recent efforts to recruit them. Based on survey data gathered from non-LIS doctorate holders currently working in U.S. and Canadian academic/research libraries, this article highlights data and trends relating to these librarians, focusing on their demographic profile, educational background, paths into librarianship, and range of positions. It is important not only to provide vital information to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
6
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 6 publications
1
6
0
Order By: Relevance
“…This underlines the perceived importance of subject expertise in advanced qualifications rather than contributing to the LIS discipline. It aligns with earlier findings that 72% of those holding PhDs in libraries came to librarianship after, not before, their doctoral studies (Lindquist & Gilman, 2008).…”
Section: The Phd and Librarianssupporting
confidence: 91%
“…This underlines the perceived importance of subject expertise in advanced qualifications rather than contributing to the LIS discipline. It aligns with earlier findings that 72% of those holding PhDs in libraries came to librarianship after, not before, their doctoral studies (Lindquist & Gilman, 2008).…”
Section: The Phd and Librarianssupporting
confidence: 91%
“…It is clear that the profile of the profession is changing (Wilder, 2018b). More professional librarians are being hired without library degrees, and instead with advanced subject degrees and/or specialized experience (Lindquist & Gilman, 2008). With this change, there will likely be a push for a transition to a new leadership model.…”
Section: Leadership Developmentmentioning
confidence: 99%
“…A 2008 article by Lindquist and Gilman surveying academic librarians who hold subject doctorates found that only 4 percent were in area studies. 34 How many of those were in Latin American studies is not known.…”
Section: Academic Backgroundmentioning
confidence: 99%